2022
DOI: 10.1002/sd.2463
|View full text |Cite
|
Sign up to set email alerts
|

Education for sustainable development: Secondary school teacher's awareness and perception of integration

Abstract: The pursuit of education for sustainable development (ESD) integration is imperative for appraising the implications and progress of the educational plan. Teachers are critical agents in delivering sustainable development content in formal education.Consequently, understanding the teachers' perspective is necessary for integration. This study analyses teachers' insights on integrating education for sustainable development. The teachers filled out a questionnaire concerning sustainable development, and data ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 99 publications
0
8
0
Order By: Relevance
“…On the contrary, a recent study of teachers' perception of ESD integration in the educative process revealed positive awareness despite poor attitudes and a detrimental state of behavior towards ESD (Khalid Malik et al, 2022). ESD's multidimensionality, lack of exposure, mindset shifts, curriculum demands, long-term commitment and leadership context contribute to the complexity of integrating ESD principles into educational leadership.…”
Section: Discussionmentioning
confidence: 97%
“…On the contrary, a recent study of teachers' perception of ESD integration in the educative process revealed positive awareness despite poor attitudes and a detrimental state of behavior towards ESD (Khalid Malik et al, 2022). ESD's multidimensionality, lack of exposure, mindset shifts, curriculum demands, long-term commitment and leadership context contribute to the complexity of integrating ESD principles into educational leadership.…”
Section: Discussionmentioning
confidence: 97%
“…This pillar also includes ele- Therefore, it is crucial to invest in the continuous development of teachers to keep them trained and motivated to do their jobs with excellence. They should be ready to deal with technological transformations in education, meeting their students and society's needs and demands (Iwu et al, 2018;Khalid Malik et al, 2022;Madziva & Thondhlana, 2017;Wang et al, 2019).…”
Section: Systematization Of the Pillars Of Qementioning
confidence: 99%
“…Therefore, raising environmental awareness is a prerequisite to understanding the human impact on the built environment and climate. Education is recognized as crucial means of raising awareness and transforming people's behaviors while education for sustainable development is believed to develop critical thinking and enhance the capabilities necessary for better‐controlled decision‐making that contributes to sustainable societies (Malik et al, 2022). As an important aspect of sustainable development in higher education, green building education is rapidly expanding worldwide.…”
Section: Xr Applications In Scmentioning
confidence: 99%